Duration measurement of vocants in infants with Cochlear Implants - Binos, Paris; Thodi, Chryssoula; Psillas, George K.; Vogazianos, Paris (My University, 2020)
Vocants are precursors to speech and are facially neutral. The presence of these speech-like vocalizations was evident during the precursors to mature phonology called “protophones”. The prosodic feature of the duration of the nuclei plays a crucial role in the shift of prelexical to mature speech since speech intelligibility is closely related to the control of duration. The aim of this work is to determine whether cochlear implants (CIs) positively trigger language acquisition and the development of verbal skills. Recent literature findings are compared and discussed with the performance of two Greek congenitally hearing-impaired infants who were matched with three normal-hearing (NH) infants. This work highlighted an important weakness of the prosodic abilities of young infants with CIs.
Keywords: vocants; prosody; duration; cochlear implant; deaf